A Study On The Prevalence Of Diabetes Mellitus Amongst Family Members Of Known Diabetics - Mehra M; Bhatnagar A.K; Rao Y.N; Garg S (Wolters Kluwer Medknow Publications, 1990)
The Present study on the prevalence of diabetes mellitus among family members of known diabetics was carried out by a house to house visit in Darya Ganji, an urban colony of Delhi. The study sample comprised family members of 213 known cases of diabetes mellitus diagnosed in an earlier survey done five months prior to the study. These cases belonged to 120 families. Of these families only 111 could be covered who had 462 persons above the age of 10 years. Of them, only 402 persons could be included in the study (non â€" response rate 12.9%). Of the total 402 subjects 48 were found to have abnormal carbohydrate tolerance (IGT + DM) to give an overall prevalence of 11.94&. The prevalence of IGT & DM was 8.7 % and 3.23% respectively. The prevalence of abnormal carbohydrate tolerance (ACT)(DM + IGT) was found to be significantly associated with age. Greater prevalence of diabetes amongst the siblings was noted when one parent was diabetic than when neither of the parents was diabetic.